Neuroanatomical variations as a function of experience in a complex daily task: A VBM and DTI study on driving experience. - Megías, Alberto; Petrova, D.; Navas, J. F.; Cándido, A.; Maldonado, A.; Catena, A. (Brain Imaging & Behavior, 2018)
Complex tasks require the learning and integration of multiple cognitive, sensory, and psychomotor skills for correct execution. Driving-related skills are developed step by step through the increase of mileage driven and the accumulation of practice in different traffic situations. The acquisition of these skills should be reflected in the brain structure. However, no previous studies have explored brain structural variations associated with driving experience. The aim of the present study was to investigate whether driving frequency, defined as average annual driving mileage, is related to neuroanatomical variations in gray matter (GM) volume and white matter (WM) integrity using voxel-based morphometry (VBM) and DTI-based fractional anisotropy (FA), respectively. We recruited 83 drivers with variable range of annual driving mileage and controlled for age, sex, handedness, IQ, time since the acquisition of driving license, use of motorcycles/mopeds and bicycles, perceived driving skills, and subjective probability of having an accident. Our results showed variations in white matter FA as a function of mileage driven. Driving experience was related to a significant increase of FA in parts of the right hemisphere superior and inferior longitudinal fasciculus, anterior thalamic radiation, forceps majors, inferior fronto-occipital fasciculus, and corticospinal tract. No significant differences were observed in gray matter volumes. FA variations were found in brain regions that have been associated with cognitive, visual, and motor processes necessary for skilled performance in driving. These results suggest that variations in white matter diffusivity can underlie the development of driving skills and safer driving.